2021
DOI: 10.1038/s41598-021-01668-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutational status of plasma exosomal KRAS predicts outcome in patients with metastatic colorectal cancer

Abstract: Liquid biopsy has become a useful alternative in metastatic colorectal cancer (mCRC) patients when tissue biopsy of metastatic sites is not feasible. In this study we aimed to investigate the clinical utility of circulating exosomes DNA in the management of mCRC patients. Exosomes level and KRAS mutational status in exosomal DNA was assesed in 70 mCRC patients and 29 CRC primary tumor and were analysed at different disease steps evaluating serial blood samples (240 blood samples). There was a significant corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In CRC, KRAS and BRAF mutation was detected from the serum exosomes of CRC patients with higher sensitivity and specificity ( Hao et al, 2017 ; Lucchetti et al, 2021 ). In addition, it has been reported that transforming growth factor receptor 2 (TGFR2) is a part of the key signal pathway in colon epithelial cells.…”
Section: Exosome Genomic Dna As a Tool For Colorectal Cancer Liquid B...mentioning
confidence: 99%
See 1 more Smart Citation
“…In CRC, KRAS and BRAF mutation was detected from the serum exosomes of CRC patients with higher sensitivity and specificity ( Hao et al, 2017 ; Lucchetti et al, 2021 ). In addition, it has been reported that transforming growth factor receptor 2 (TGFR2) is a part of the key signal pathway in colon epithelial cells.…”
Section: Exosome Genomic Dna As a Tool For Colorectal Cancer Liquid B...mentioning
confidence: 99%
“…The author also confirmed that KRAS mutation disappeared rapidly after the first chemotherapy cycle. However, it is necessary to closely monitor secondary drug resistance after anti-EGFR treatment to stop this treatment as soon as possible ( Lucchetti et al, 2021 ). Therefore, exosome gDNA can be used as an innovative tool to monitor the diagnosis, drug resistance, and prognosis of CRC patients during treatment.…”
Section: Exosome Genomic Dna As a Tool For Colorectal Cancer Liquid B...mentioning
confidence: 99%
“…CRC is a common gastrointestinal malignancy occurring in the colon [ 18 ]. CRC inchoate symptom is more not apparent and often already was in progress period when seeing a doctor, right now commonly used remedial measure [ 2 ]. To improve the resection rate, reduce the recurrence rate, and improve the survival rate, the treatment of intermediate and advanced CRC is based on surgery, supplemented by chemotherapy, immunotherapy, traditional Chinese medicine, and other supportive therapies [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC), as one of the most aggressive cancers with poor prognosis, causes a large number of deaths worldwide and affects millions of people every year [ 1 , 2 ]. CRC mainly affects the distal rectum, sigmoid colon, and descending colon [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of EV-derived DNA reliably reflect the mutational state in the tumor of origin (García-Silva et al, 2020). For example, EGFR mutation was presented in plasma exosomes from lung cancer (Krug et al, 2018;Purcell et al, 2021) and cerebrospinal fluid EVs from glioblastoma (Figueroa et al, 2017), and KRAS mutation was presented in plasma exosomes from pancreatic cancer (Allenson et al, 2017) and colorectal cancer (Lucchetti et al, 2021). Some EV-derived DNA is tissuespecific.…”
Section: Component Specificitymentioning
confidence: 99%